Cor triatriatum sinister, not mitral stenosis, in an adult with previous Sydenham's chorea: diagnosis and preoperative assessment by cross sectional echocardiography. Issue 7 (July 1992) - De Belder, Mark A; Argano, Vincenzo; Burrell, Christopher J
Abstract : In cor triatriatum sinister, one of the rarest congenital cardiac anomalies, a membrane divides the left atrium into a pulmonary venous component above and the vestibule below. The importance of the anomaly lies in the effects of the resultant pulmonary venous obstruction that usually present in the first year of life and can mimic obstructed total anomalous venous drainage or congenital mitral stenosis. A case presented as mitral stenosis in the third decade of life, ten years after a well documented episode of Sydenham's chorea. The diagnosis was made rapidly by transthoracic echocardiography and transoesophageal echocardiography was used for complete assessment. Cardiac catheterisation added nothing to the non-invasive diagnosis or the preoperative assessment. Uncomplicated corrective surgery was undertaken.